School effectiveness for whom? : challenges to the school effectiveness and school improvement movements - Slee, Roger; Weiner, Gaby; Tomlinson, Sally (Falmer Press, 1998)
A collection of essays that challenge the school effectiveness and school improvement movements. Particular criticism is levelled at the disassociation of what goes on in schools from the world at large.